The influence of sars-cov-2 pandemic restrictions on students in choosing the professional path - Mihai Constantinescu (Annals of the “Ştefan cel Mare” University: Physical Education and Sport Section - The Science and Art of Movement, 2022)
This investigative approach aims to highlight the influence that socialization has through physical presence during undergraduate studies. We also want to analyze the factors that were unfavorable to the teaching act as well as the decisive role in choosing the career path for students who finish their studies. At the same time, we will highlight some aspects of the issues that accompanied the teaching act during the SARS-COV-2 pandemic.